B vitamins intake and cognitive status among elderly in agricultural settlements - Lokman, Nur Fatin Atiqah; Hamirudin, Aliza Haslinda; Sidek, Suriati; Zainudin, Norain; A. Rahman, Nor Azlina (Kulliyyah of Allied Health Sciences, IIUM, 2019)
Introduction: The number of elderly who have been diagnosed with cognitive impairment are increasing in Malaysia and becoming a matter of a great concern for the health sectors. One of the ways to overcome this rising problem is by identifying one of its risk factors which is inadequate dietary intake particularly B vitamins (folate, vitamin B12 and B6). This study aimed to identify total B vitamins intake and its association with cognitive status of the elderly in agricultural settlements (FELDA) in Kuantan, Pahang. Methods: Seventy-eight elderly aged ≥60 years old were recruited in this study using convenience sampling. A home visit was done and subjects were interviewed using a questionnaire on their demographic data. Dietary history method was used to collect information on dietary intake; whilst the cognitive status was assessed using the Malay version of Mini Mental State Examination (MMSE). Dietary intake was analyzed using Nutritionist Pro Software version 3.00. The total B vitamins intake data were then compared with Recommended Nutrient Intakes for Malaysia (RNI 2017). Results: Majority of the subjects have inadequate total folate (93.6%), vitamin B6 (92%) and vitamin B12 (63%) intake. The comparison between total B vitamins intake and RNI showed significant differences (p = 0.001) except for vitamin B12 (p= 0.398). Most of the subjects have normal cognitive function as 62.8% of them achieved normal MMSE score (>24 out of 30 marks). No significant association between B vitamins intake and cognitive status of the elderly subjects were identified. Conclusions: High prevalence of inadequate B vitamins intake is evident among elderly living in agricultural settlements. Hence, a well-structured nutrition education programmes and activities need to be conducted to ensure optimum nutritional and cognitive status among the elderly.